Sophisticated adaptations of Gregarina cuneata (Apicomplexa) feeding stages for epicellular parasitism - Valigurová, Andrea (PloS one, 2012)
BACKGROUND: Gregarines represent a very diverse group of early emerging apicomplexans, parasitising numerous invertebrates and urochordates, and are considered of little practical significance. Recently, they have gained more attention since some analyses showed that cryptosporidia are more closely related to the gregarines than to coccidia. METHODOLOGY/PRINCIPAL FINDINGS: Using a combined microscopic approach, this study points out the spectacular strategy of Gregarina cuneata for attachment to host tissue and nutrient acquisition while parasitising the intestine of yellow mealworm larvae, and reveals the unusual dynamics of cellular interactions between the host epithelium and parasite feeding stages. Trophozoites of G. cuneata develop epicellularly, attached to the luminal side of the host epithelial cell by an epimerite exhibiting a high degree of morphological variability. The presence of contractile elements in the apical region of feeding stages indicates that trophozoite detachment from host tissue is an active process self-regulated by the parasite. A detailed discussion is provided on the possibility of reversible retraction and protraction of the eugregarine apical end, facilitating eventual reattachment to another host cell in better physiological conditions. The gamonts, found in contact with host tissue via a modified protomerite top, indicate further adaptation of parasite for nutrient acquisition via epicellular parasitism while keeping their host healthy. The presence of eugregarines in mealworm larvae even seems to increase the host growth rate and to reduce the death rate despite often heavy parasitisation. CONCLUSIONS/SIGNIFICANCE: Improved knowledge about the formation of host-parasite interactions in deep-branching apicomplexans, including gregarines, would offer significant insights into the fascinating biology and evolutionary strategy of Apicomplexa. Gregarines exhibit an enormous diversity in cell architecture and dimensions, depending on their parasitic strategy and the surrounding environment. They seem to be a perfect example of a coevolution between a group of parasites and their hosts.
Keywords: symbióza; Protein Binding; Host-Pathogen Interactions; Apicomplexa; Actins; epitelové buňky; Epithelium; epitel; Tenebrio; Adaptation, Physiological; Epithelial Cells; Myosins; fyziologická adaptace; aktiny; vazba proteinů; Animals; interakce hostitele a patogenu; zvířata; Protein Transport; Symbiosis; myosiny; transport proteinů